Effects of ryegrass and forage black oats cultivation on root diseases and yield of wheat - dos Santos, Henrique Pereira; Reis, Erlei Melo (Pesquisa Agropecuaria Brasileira, 1994)
During five seasons (1985 to 1989), the effects of several cultivation systems with ryegrass (Lolium multiforum) and with black oats (Avena strigosa) for forage were evaluated in the National Center for Research on Wheat (EMBRAPA), Passo Fundo, RS, for root disease intensity and grain yield of wheat (Triticum aestivum). The treatments consisted of the following cultivation systems for wheat: 1) monoculture of wheat; 2) rotation of a winter crop with wheat and two with ryegrass; 3) rotation of a winter cereal with wheat and two with black oats; 4) rotation of a winter crop with wheat and three with black oats. The wheat with two consecutive winter crops with ryegrass showed, in absolute values, a higher percentage of root disease intensity and less grain yield. For the parameters studied, this treatment had a worse performance than wheat in monoculture.
Keywords: crop rotation; root system